Penglibatan Organisasi Bukan Kerajaan (NGO) Dalam Bantuan Kemanusiaan Ke Palestin (Aman Palestin Berhad): Involvement of Non-Governmental Organizations (NGO) In Humanitarian Ad to Palestine (Aman Palestin Berhad) - Baharom, Adlin Shaimi; Mohd Zarawi, Siti Nur Maisarah (Journal Al-Muqaddimah, 2024)
This era of globalization has seen a great increase in Non-Governmental Organizations (NGOs) in developing the country. It started as a small enterprise but has gradually developed in various social, economic and political fields. Each NGO moves in various forms depending on its own mission and purpose. Humanitarian NGOs are the most active NGOs in various countries and are the most important element in ensuring that the harmony of life is well preserved. This causes Malaysian NGOs to be involved in helping to channel humanitarian aid to the victims of the atrocities of the Zionist regime, namely the Palestinian people and the victims of the atrocities of the enemy of Islam in other countries. This study focuses on the Malaysian NGO movement Aman Palestin. The study will include several activities, policies and contributions given to the Palestinian people. The role of NGOs in fighting for the truth, raising awareness issues and providing assistance to some extent has opened the eyes of the whole world including some leaders to ensure that the Palestinian people's dream of achieving independence and freedom will come true one day.